Attitudes and Beliefs of Nonspecialist and Specialist Trainee Health and Physical Education Teachers Toward Obese Children: Evidence for "Anti‐Fat" Bias. (September 2015) - Lynagh, Marita; Cliff, Ken; Morgan, Philip J.
ABSTRACT BACKGROUND The aim of this study was to assess the beliefs and attitudes of preservice health and physical education (HPE) specialist and nonspecialist schoolteachers toward obese children. METHODS A total of 177 nonspecialist and 62 HPE specialist trainee teachers completed a series of pen‐and‐paper validated measures of attitudes and beliefs toward obese children. RESULTS Both groups of preservice teachers reported strong implicit and moderate explicit anti‐fat bias. Enrollment in the HPE specialist degree was found to be a significant predictor of both implicit bad/good anti‐fat bias (β = 3.97, p = .002) and implicit bias on the stupid/smart scale (β = 2.983, p = .016) of the IAT. Beliefs that obese children were less healthy, more self‐conscious, and less satisfied with themselves were strongly endorsed by the majority of participants. HPE specialists were found to have significantly lower expectations for obese children in regard to "reasoning" (mean difference = 0.21, p = .0107) and "cooperation" skills (mean difference = 0.25, p = .0354) compared to nonspecialist trainees. CONCLUSIONS This study is the first to document the strong anti‐fat bias of both preservice nonspecialist and HPE specialist teachers. It is also the first to find that preservice HPE specialist teachers have stronger anti‐fat biases and differential expectations regarding particular abilities of obese children, compared to nonspecialists.